# SOLUTION: Question: 4- a-b/a+4 = a^2-6/a+4 Here's what I've got so far. LCM is a+4 (a+4)(4- a-b/a+4) = (a=4)(a^2-6/a+4) 4(a=4) - a-b/a+4 (a+4) = (a+4)a^2+6/a+4= 4a +4 * 4 - (a-b

Algebra ->  -> SOLUTION: Question: 4- a-b/a+4 = a^2-6/a+4 Here's what I've got so far. LCM is a+4 (a+4)(4- a-b/a+4) = (a=4)(a^2-6/a+4) 4(a=4) - a-b/a+4 (a+4) = (a+4)a^2+6/a+4= 4a +4 * 4 - (a-b      Log On

 Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations! Ad: Mathway solves algebra homework problems with step-by-step help!

 Question 344861: Question: 4- a-b/a+4 = a^2-6/a+4 Here's what I've got so far. LCM is a+4 (a+4)(4- a-b/a+4) = (a=4)(a^2-6/a+4) 4(a=4) - a-b/a+4 (a+4) = (a+4)a^2+6/a+4= 4a +4 * 4 - (a-b) = a^2 -6 Then I'm supposed to simplify, I've got the 3a +16???? What do I do with the b? After simplifying, I'm supposed to write the result as a quadratic equation by 3a and 16 from sides and simplifying, then solve the quadratic equation. Please help, I'm stumped. I also have not figured out how to post a thank you for help on this site.Answer by stanbon(60771)   (Show Source): You can put this solution on YOUR website! 4- (a-6)/(a+4) = (a^2-6)/(a+4) =============================== Multiply thru by (a+4) to get: 4(a+4) - (a-6) = a^2-6 --- 4a+16 -a+6 = a^2-6 3a+16+6 = a^2-6 a^2-3a-22 = 6 a^2-3a-28 = 0 (a-7)(a+4) = 0 a = 7 or a = -4 --- Only a=7 is a solution. ======================= Cheers, Stan H.